Medical grade vs off-the-shelf color displays: influence on observer performance and visual search. - Krupinski EA (Journal of Digital Imaging, 2009)
The goal of this study was to compare diagnostic accuracy of radiologists viewing clinical images on a top-of-the-line medical-grade vs a top-of-the-line commercial off-the-shelf (COTS) color display with the luminance values set to simulate a display that had been in use for 1 year. A set of 50 digital radiography chest images was selected for use in the study, half containing a solitary pulmonary nodule and half nodule-free. The images were displayed twice to each of six observers, once on each display. Eye position was recorded on a subset of the images. Overall, there was a statistically significant difference (F = 4.1496, p = 0.0471) between the medical-grade color display and the COTS color display in terms of receiver operating characteristic area under the curve values, with the medical-grade display yielding higher diagnostic accuracy. Total viewing time did not differ significantly, but eye position data revealed differences, suggesting better search and decision-making efficiency with the medical-grade display. Medical-grade color displays at 1 year old yield better diagnostic and search efficiency than COTS color displays and thus are recommended for primary reading if color displays are to be used.